Patron-Client Social Relationship Between Palm Oil Farmers And Tauke In Kreung Itam Village Tadu Raya District Nagan Raya District - Khori Suci Maifianti; Dedy Darmansyah; Ikhwanul Muslimin (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2021)
Krueng Itam village is one of the villages where the majority of the residents work as palm oil farmers and depend on palm oil plantations. In marketing to sell FFB (Fresh Fruit Bunch) palm oil farmers still rely on collector traders (agents) which in this case is referred to by the term